Огляд методів розпізнавання рухомого об’єкту - Кобзєв, К. В. (ХНУРЕ, 2021)
The work reviews and analyzes features in field of object recognition. First, recognition in video stream and factors that complicate this process are considered. The following is a brief overview of RGB color description model. The image recognition on basis of an artificial neural network is briefly analyzed and difficulties in implementation of this method are revealed. Methods of genetic programming for image processing and features of application are described.
Keywords: методи розпізнавання; рухомі об'єкти